Large deletions of the PROS1 gene in a large fraction of mutation-negative patients with protein S deficiency - Johansson, Anna M.; Hillarp, Andreas; Säll, Torbjörn; Zöller, Bengt; Dahlbäck, Björn; Halldén, Christer (Thrombosis and Haemostasis, 2005)
Protein S deficiency is an autosomal dominant disorder that results from mutations in the PROS1 gene. Conventional mutation detection techniques fail to detect a pathogenic PROS1 mutation in approximately 50% of cases. The present study investigates whether large deletions of PROS1 are found in families where mutations in the PROS1 gene have not been found despite sequencing. For this purpose, a dense set of SNP and microsatellite markers were used in segregation analysis to identify deletions. Large deletions were identified by this technique in three out of eight investigated families (38%). The deletions encompassed at least 35 kb, 437 kb and 449 kb respectively. The deletions were confirmed by quantitative PCR. Haplotype analysis showed that the three large deletions and the five other disease haplotypes were all different. All of the eight disease haplotypes co-segregated with protein S deficiency, but each of the five non-deletion haplotypes were present also in normal individuals. In conclusion: Large deletions of PROS1 are relatively common in protein S deficiency patients and screening for large deletions in PROS1 mutation-negative individuals are therefore warranted.
Keywords: Deletion; mutation; protein S deficiency; PROS1